Host use patterns by the European woodwasp, Sirex noctilio, in its native and invaded range. - Matthew P Ayres; Rebeca Pena; Jeffrey A Lombardo; Maria J Lombardero (PLoS ONE, 2014)
Accelerating introductions of forest insects challenge decision-makers who might or might not respond with surveillance programs, quarantines, eradication efforts, or biological control programs. Comparing ecological controls on indigenous vs. introduced populations could inform responses to new introductions. We studied the European woodwasp, Sirex noctilio, which is not a pest in its native forests, is a serious invasive pest in the southern hemisphere, and now has an uncertain future in North America after its introduction there. Indigenous populations of S. noctilio (in Galicia, Spain) resembled those in New York in that S. noctilio were largely restricted to suppressed trees that were also dying for other reasons, and still only some dying trees showed evidence of S. noctilio: 20-40% and 35-51% in Galicia and New York, respectively. In both areas, P. sylvestris (native to Europe) was the species most likely to have attacks in non-suppressed trees. P. resinosa, native to North America, does not appear dangerously susceptible to S. noctilio. P. radiata, which sustains high damage in the southern hemisphere, is apparently not innately susceptible because in Galicia it was less often used by native S. noctilio than either native pine (P. pinaster and P. sylvestris). Silvicultural practices in Galicia that maintain basal area at 25-40 m(2)/ha limit S. noctilio abundance. More than 25 species of other xylophagous insects feed on pine in Galicia, but co-occurrences with S. noctilio were infrequent, so strong interspecific competition seemed unlikely. Evidently, S. noctilio in northeastern North America will be more similar to indigenous populations in Europe, where it is not a pest, than to introduced populations in the southern hemisphere, where it is. However, S. noctilio populations could behave differently when they reach forests of the southeastern U.S., where tree species, soils, climate, ecology, management, and landscape configurations of pine stands are different.